Multiple Café au Lait Spots in a Group of Fair‐Skinned Children without Signs or Symptoms of Neurofibromatosis Type 1. Issue 5 (28th July 2016) - St. John, Jessica; Summe, Heather; Csikesz, Courtney; Wiss, Karen; Hay, Beverly; Belazarian, Leah
Abstract: Background: The presence of six or more café au lait (CAL) spots is a criterion for the diagnosis of neurofibromatosis type 1 (NF‐1). Children with multiple CAL spots are often referred to dermatologists for NF‐1 screening. The objective of this case series is to characterize a subset of fair‐complected children with red or blond hair and multiple feathery CAL spots who did not meet the criteria for NF‐1 at the time of their last evaluation. Methods: We conducted a chart review of eight patients seen in our pediatric dermatology clinic who were previously identified as having multiple CAL spots and no other signs or symptoms of NF‐1. Results: We describe eight patients ages 2 to 9 years old with multiple, irregular CAL spots with feathery borders and no other signs or symptoms of NF‐1. Most of these patients had red or blond hair and were fair complected. All patients were evaluated in our pediatric dermatology clinic, some with a geneticist. The number of CAL spots per patient ranged from 5 to 15 (mean 9.4, median 9). Conclusion: A subset of children, many with fair complexions and red or blond hair, has an increased number of feathery CAL spots and appears unlikely to develop NF‐1, although genetic testing was not conducted. It is important to recognize the benign nature of CAL spots in these patients so that appropriate screening and follow‐up recommendations may be made.